Optimizing the Implementation of Local Tax Collection (Study on the Installation of a Tapping Box Tool on Hotel Taxes in Padang Lawas Regency) - Maya Dian Eka Sari; Andri Soemitra (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
Regional Original Revenue (PAD) consists of 3 main aspects, namely regional taxes, regional levies and the results of the management of regional property, as well as the management of separate regional assets. Optimizing tourism potential is one of the strategies to increase regional income (Pratama, 2016). This study aims to find out how to optimize the implementation of local tax collection (Hotel Tax) by installing the Tappix Box tool. This study uses a literature study approach to answer the research objectives. The literature study conducted in this study is a form of research conducted by collecting journal articles with the theme in accordance with the research objectives, namely Optimizing the Implementation of Local Tax Collection. In optimizing the implementation of local tax collection, especially hotel taxes, there are several obstacles and obstacles. The obstacles that occur will make business actors, namely the presence of business actors for various reasons, feeling distrusted, and lack of knowledge of the importance of regional development. In addition, there are unscrupulous actors who turn off wiretapping tools for the purpose of the business actors themselves. Efforts are made to minimize obstacles or obstacles in tax collection, namely providing sanctions, business permits, permanent business permits if business actors refuse and turn off wiretapping, and carry out continuous socialization to business actors.